Student Thinking Process In Solving Open-Ended Problem Of The PISA Model Of Space And Shape Contents Based On Adversity Quotient (AQ) - Kusumawardani, Linda; Nanik Yuliati, Susanto, (International Journal of Scientific Research and Management (IJSRM), 2017)
The purpose of this research is to describe the thinking process of students with high AQ (Climber), medium AQ (Camper), and low AQ (Quitter) from grade VIII-C students of Junior High School 2 Jember in solving open-ended problem of PISA model of Space and Shape based on Polya's problem- solving. This research is a descriptive research with the qualitative approach. Data collection methods which are used are tests, interviews, and questionnaires. In this research, data analysis is done using descriptive analysis. The data analyzed in this research is the answer sheet for the student about the problem of mathematical problem-solving test and interview result. The results of the analysis show that each subject is different based on the thinking process. A Student with high AQ (Climber) shows a lot of equilibrium in it through the stage of assimilation and accommodation. Students with medium AQ (Camper) show a lot of assimilation and accommodation conditions are also slightly disequilibrium. Students with low AQ (Quitter) show a lot of disequilibrium, assimilation, accommodation and a little equilibrium